NAVIGATING THE SUCCESSION PROCESS IN FAMILY BUSINESSES: A CASE STUDY OF THE ICON - Sinar Dharmayana Putra; Erwin; Maichal; St Salmah Sharon (Accounting Profession Journal (APAJI), 2024)
This research explores the dynamics of trust in the succession process of a family business at The Icon. Employing descriptive qualitative methodology, the study delves into how trust is built and maintained through various stages of the succession process. The successor did not receive theoretical training but learned directly by observing their parents and the employees at The Icon. The mother of the successor played a crucial role in providing hands-on training, particularly in social media marketing. Every piece of content must be approved by her to maintain high standards and avoid misunderstandings that could damage the business's reputation. Additionally, she supervises the food photoshoots to ensure the menu presentations are aesthetically pleasing. The successor is also trained in food art classes to enhance their skills. The responsibility of ensuring smooth operations and resolving issues at The Icon is a significant part of the successor’s role. For instance, when a customer complained about cold food, the successor handled the situation professionally by offering a replacement and complimentary food. The findings suggest that the successor exhibits a high level of responsibility, working diligently to address and resolve challenges, thereby ensuring the continued success and reputation of The Icon.